The Relationship between the Stock Market and Consumption. Issue 1 (8th April 2013) - Alghalith, Moawia; Polius, Tracy
<x xml:space="preserve">Abstract</x> This paper examines the interaction between consumption and the price/return of stocks. In so doing, we utilise an advanced theoretical and empirical framework. It is worth noting that previous literature used simple linear regressions without a rigorous theoretical basis. Consequently, we present a sophisticated non‐linear dynamic model as the theoretical basis of our empirical results.